Photo-vibrational spectroscopy using quantum cascade laser and laser Doppler vibrometer - Liu, Huan (2019)
Photoacoustic/photothermal spectroscopy is an established technique for detection of chemicals and explosives. However, prior sample preparation is required and the analysis is conducted in a sealed space with a high-sensitivity sensor coupled with a lock-in amplifier, limiting the technique to applications in a controllable laboratory environment. Hence, this technique may not be suitable for defense and security applications where the detection of explosives or hazardous chemicals is required in an open environment at a safe standoff distance. In this study, chemicals in various forms were excited by an intensity-modulated quantum cascade laser (QCL), while a laser Doppler vibrometer (LDV) was applied to detect the vibration signal resulting from the photocoustic/photothermal effect. The photo-vibrational spectrum obtained by scanning the QCL’s wavelength in MIR range, coincides well with the corresponding spectrum obtained using typical FTIR equipment. The experiment in short and long standoff distances demonstrated that the LDV is a capable sensor for chemical detection in an open environment.